Effect of confinement on the efficiency of bottle-shaped struts. Issue 18 (22nd June 2018) - Sahoo, Dipak Kumar; Varghese, Biju P.
Abstract : Isolated strut tests were performed to study the effect of plain concrete lateral confinement on the efficiency of two-dimensional (2D) and three-dimensional (3D) bottle-shaped struts. For the 2D struts, thin plain concrete panels of varying width were tested to failure under in-plane compression. For the 3D struts, short square columns of varying cross-section were tested to failure under axial compression. The strut efficiency in short columns was found to increase with cross-section as expected, although the increase became insignificant beyond a certain limit. However, the strut efficiency in the panels increased with an increase in panel width only up to half the panel height and thereafter reduced significantly. Supported by finite-element modelling, the results revealed the hitherto unknown phenomenon that excessive confinement negatively impacts on the efficiency of wide bottle-shaped struts only in planar (plane stress) concrete members.